Hubungan Pola Makan Anak dan Status Gizi Anak Usia Sekolah - Permatasari, Indah; Ritanti, Ritanti; Siregar, Tatiana (STIKES Ngesti Waluyo, 2023)
Nutritional status is a state of balance between the intake of nutrients in food and the body's needs. This nutritional status can be influenced by many factors, one of which is the child's diet. School-age children are one of the groups of children who are vulnerable to nutritional problems. The purpose of this study was to describe the characteristics of the respondents, and the relationship between children's eating patterns and the nutritional status of school-age children at MI Sa'adatudarain Limo. The method used in this research was quantitative study using Cross Sectional design with a sample of 79 respondents through Stratified Random Sampling technique. Data were collected directly by enumerators (nursing students and classroom teachers, as well as the research team) through the Food Frequency Questionnaire (FFQ) and anthropometric measurements. This study used univariate analysis to determine the distribution of frequencies and averages, and bivariate analysis using Chi Square test. The results showed that there was a significant relationship between children's eating patterns and the nutritional status (p-value=0.007) of school-age children at MI Sa'adatudarain Limo. Further research can be done to analyze other factors that can affect nutritional status by using a more complete method, for example the Mixed Method.